1979
DOI: 10.3109/00365527909179882
|View full text |Cite
|
Sign up to set email alerts
|

A Bile-acid-rich High-density Lipoprotein (HDL) in Acute Hepatitis

Abstract: Severe liver dysfunction is often associated with alterations of plasma lipids and lipoproteins. In this study the high-density lipoprotein (HDL) class has been further investigated. HDL from patients with acute, cholestatic hepatitis (n = 10) was isolated and compared with that of normals. Lipid and protein analyses were performed during the acute stage of the disease, with consequent follow-up studies. It was found that (1) only apo A-I was decreased by 50% in the isolated HDL fractions, whereas apo A-II rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The position of the 3-␣ hydroxyl group in the steroid nucleus, specifi cally in cholate and taurocholate derivatives, was found to promote HDL binding ( 40 ), particularly the more hydrophilic BAs. In acute cholestatic hepatitis, HDL BAs were found to be increased more than 10-fold, which was reversible with treatment ( 41 ). In normolipidemic subjects, 11% of total BAs in serum were observed bound to HDL ( 39 ).…”
Section: Hdl Lipidomementioning
confidence: 74%
“…The position of the 3-␣ hydroxyl group in the steroid nucleus, specifi cally in cholate and taurocholate derivatives, was found to promote HDL binding ( 40 ), particularly the more hydrophilic BAs. In acute cholestatic hepatitis, HDL BAs were found to be increased more than 10-fold, which was reversible with treatment ( 41 ). In normolipidemic subjects, 11% of total BAs in serum were observed bound to HDL ( 39 ).…”
Section: Hdl Lipidomementioning
confidence: 74%
“…It is believed that apoA‐I is controlled at the post‐translational level and liver damage decreases the apoA‐I conversion from other isoforms 19,21 . In a study performed in adults with acute, cholestatic hepatitis, it was found that only apo A‐I was decreased by 50% in the isolated HDL fractions, whereas apo A‐II remained unchanged 22 . The decrease was fully reversible and considered as a sensitive marker for the degree of disturbance and restoration of liver function 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed in adults with acute, cholestatic hepatitis, it was found that only apo A‐I was decreased by 50% in the isolated HDL fractions, whereas apo A‐II remained unchanged 22 . The decrease was fully reversible and considered as a sensitive marker for the degree of disturbance and restoration of liver function 22 . In our study, serum apo A‐I level was lower in children with AVH compared to healthy children and was lower in the case of cholestasis.…”
Section: Discussionmentioning
confidence: 99%